The Impact of the Implementation of Student Tuition Payment Information Systems on the Quality of Financial Reports: A Case Study at Universitas Komputer Indonesia - Adeh Ratna Komala; Mari Maryati (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research is to see the impact of implementing a student tuition payment system on the quality of financial reports at the Universitas Komputer Indonesia. This is done because students are customers whose loyalty must be maintained. Efforts are being made to provide satisfaction to students by providing transparent and accountable financial report information. The research method used is a survey method using a questionnaire via google form. Respondents were 28 study programs at Universitas Komputer Indonesia as users of the system. The data analysis was carried out through descriptive and verification analysis. Data processing using SEM PLS. The results showed the level of closeness (correlation coefficient) between the student tuition payment system and the quality of financial reports. From these results it can be said that the student tuition payment system is very helpful for the Universitas Komputer Indonesia in producing quality financial reports so that it can make it easier for users to make decisions. Universitas Komputer Indonesia continues to innovate in developing an integrated student tuition payment information system so that the resulting financial reports can provide useful information for the user. The student tuition payment information system has been proven to have improved the quality of information that is accurate, relevant, timely and complete. In addition, the student tuition payment information system created by the Universitas Komputer Indonesia has made it easier for system users to carry out their work so as to cut time more efficiently.